2022
DOI: 10.15252/emmm.202216796
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil‐derived IL ‐4 is necessary to establish the inflammatory structure in innate inflammation

Abstract: Pathogen‐induced inflammation comprises pro‐ and anti‐inflammatory processes, which ensure pathogen removal and containment of the proinflammatory activities. Here, we aimed to identify the development of inflammatory microenvironments and their maintenance throughout the course of a toll‐like receptor 2‐mediated paw inflammation. Within 24 h after pathogen‐injection, the immune cells were organized in three zones, which comprised a pathogen‐containing “core‐region”, a bordering proinflammatory (PI)‐region and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 52 publications
(72 reference statements)
3
27
0
Order By: Relevance
“…The post-bleaching images were subtracted from the subsequent fluorescence image. The antibodies used for the MELC procedure are listed in Table S1 and have been validated previously (Kolbinger et al, 2022(Kolbinger et al, , 2023Kornstädt et al, 2020;Pierre et al, 2017;Pierre & Scholich, 2010). Stainings without secondary antibodies served as negative controls for COX-1 and COX-2 antibodies.…”
Section: High-content Immunohistochemistrymentioning
confidence: 99%
See 4 more Smart Citations
“…The post-bleaching images were subtracted from the subsequent fluorescence image. The antibodies used for the MELC procedure are listed in Table S1 and have been validated previously (Kolbinger et al, 2022(Kolbinger et al, , 2023Kornstädt et al, 2020;Pierre et al, 2017;Pierre & Scholich, 2010). Stainings without secondary antibodies served as negative controls for COX-1 and COX-2 antibodies.…”
Section: High-content Immunohistochemistrymentioning
confidence: 99%
“…To determine whether the observed quantitative changes indicated broader alterations in the immune cell network, we analysed the likelihood of finding different cell types adjacent to each other compared to randomized versions of the same tissue (Figure S4) (Schapiro et al, 2017). Given that M1-like and M2-like macrophages are key cells types that determine the regional structure during zymosan-induced inflammation (Kolbinger et al, 2023), we initially focused on cell clusters defined by combinations of markers characterizing clusters as M1-like macrophages (Siglec F À /F4-80 + /CD86 + / CD206 À ), M2-like macrophages (Siglec F À /F4-80 + /CD86 À /CD206 + ) and non-polarized M0 macrophages (Siglec F À /F4-80 + /CD86 + / CD206 + ). Linear distance maps of the relative distance between zymosan and these cell clusters in control mice revealed that M1-like macrophages accumulated in the direct neighbourhood of zymosan whereas M2-like macrophages were excluded from this area (Figure 3a).…”
Section: Meloxicam Treatment Removes the Pi Regionmentioning
confidence: 99%
See 3 more Smart Citations